Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

If (2,1) be a solution of the equation then , if (x,y) are replaced by (2,1) then LHS must be equal to RHS, lets see;

2(2)+1=5

=> 4+1=5

=>5=5

wow!!! LHS=RHS;

Thus, the given point is a solution of the equation.

2(2)+1=5

=> 4+1=5

=>5=5

wow!!! LHS=RHS;

Thus, the given point is a solution of the equation.

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

IN (2,1) 2 INDICATES THE ABSICCA OR THE X-COORDINATE AND 1 INDICATES THE ORDINATE OR Y-COORDINATE

NOW WE CAN SUBSTITUTE (2,1) IN THE EQUATION 2X+Y=5

AFTER SUBSTITUTING THE POINTS IF LHS=RHS THEN THE POINT IS A SOLUTION OF THE GIVEN EQUATION.

2X+Y⇒2(2)+1(1)=4+1=5

AS LHS=RHS THE POINT (2,1) IS A SOLUTION OF THE EQUATION 2x+y=5

NOW WE CAN SUBSTITUTE (2,1) IN THE EQUATION 2X+Y=5

AFTER SUBSTITUTING THE POINTS IF LHS=RHS THEN THE POINT IS A SOLUTION OF THE GIVEN EQUATION.

2X+Y⇒2(2)+1(1)=4+1=5

AS LHS=RHS THE POINT (2,1) IS A SOLUTION OF THE EQUATION 2x+y=5